ANALISIS AGILE GOVERNANCE DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SURAKARTA - Almira, Puspa; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
The low use of the Dukcapil Dalam Genggaman application by the people of Surakarta City and the emergence of online service problems related to service flow and application servers are separate problems in governance at the Surakarta City Population and Civil Registration Service. The concept of Agile Governance emerged as a guideline in implementing governance. Agile Governance refers to the concept of governance that is flexible, fast and responsive in facing unexpected changes to meet the demands and needs of an ever-growing society. This research aims to analyze the implementation of Agile Governance and identify supporting and inhibiting factors for Agile Governance in the Dukcapil Dalam Genggaman application. This research uses a qualitative descriptive method with data collection techniques through interviews, observation and documentation. The research results show that the Disdukcapil of Surakarta City has implemented three principles optimally, namely good enough governance, human focused and systematic and adaptive approach. There are two principles that have not been implemented optimally, namely based on quick wins and simple design and continuous refinement. The supporting factors are competent human resources, performance monitoring by leadership, systems created directly by experts and community compliance. The inhibiting factors are the applicable legal basis, communication and the government's lack of awareness of the importance of application performance assessment. The recommendation given is to hold regular evaluation meetings to improve poor communication patterns and establish application Key Performance Indicators as work guidelines to create optimal application performance.